2016
DOI: 10.1016/j.xphs.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Sandwich-Cultured Hepatocytes as a Tool to Study Drug Disposition and Drug-Induced Liver Injury

Abstract: Sandwich-cultured hepatocytes (SCH) are metabolically competent and have proper localization of basolateral and canalicular transporters with functional bile networks. Therefore, this cellular model is a unique tool that can be used to estimate biliary excretion of compounds. SCH have been used widely to assess hepatobiliary disposition of endogenous and exogenous compounds and metabolites. Mechanistic modeling based on SCH data enables estimation of metabolic and transporter-mediated clearances, which can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 164 publications
(211 reference statements)
0
42
0
Order By: Relevance
“…For example, MRP3-6 are induced in liver biopsies from NASH patients, similar to findings in a rodent model of NASH. 176,180182 Similarly, Mrp1 mRNA is increased ~5-fold compared to control animals. 176 Functional drug disposition studies corroborate these reports as evidenced by increased plasma acetaminophen glucuronide concentrations in diet-induced NASH animals attributable to increased Mrp3 expression.…”
Section: Introductionmentioning
confidence: 96%
“…For example, MRP3-6 are induced in liver biopsies from NASH patients, similar to findings in a rodent model of NASH. 176,180182 Similarly, Mrp1 mRNA is increased ~5-fold compared to control animals. 176 Functional drug disposition studies corroborate these reports as evidenced by increased plasma acetaminophen glucuronide concentrations in diet-induced NASH animals attributable to increased Mrp3 expression.…”
Section: Introductionmentioning
confidence: 96%
“…Model-independent parameters describing the overall hepatobiliary disposition of TCA in SCHH were calculated using eqs. 1 and 2 (Liu et al, 1999;Yang et al, 2016) as well as eq. 3.…”
Section: Methodsmentioning
confidence: 99%
“…(Yu et al, 2002;Modica et al, 2010), multidrug resistanceassociated protein 2 (MRP2) (Modica et al, 2010;Liu et al, 2014), and organic solute transporter (OSTa/b) (Boyer et al, 2006;Modica et al, 2010;Liu et al, 2014) in hepatic cell lines and primary human hepatocytes. Sandwich-cultured human hepatocytes (SCHH) are a physiologically relevant model that maintains transporter function, morphology, and regulatory machinery (LeCluyse et al, 2000;Yang et al, 2016) and therefore, is an ideal system to study the regulation of bile acid transporters after nonacute (.24-hour) treatment of hepatocytes with FXR agonists. Recent studies revealed that OCA and CDCA treatment of SCHH for 72 hours increased mRNA expression of OSTa/b and BSEP with minor changes in MRP3, MRP4, and sodium taurocholate cotransporting polypeptide (NTCP) (Jackson et al, 2016;Zhang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Of more pharmaco-toxicological relevance are drug transporter assays, which offer the advantage to combine testing of polarity and hepatocellular functionality. In this respect, functionality testing of the sinusoidal sodium-taurocholate cotransporter, the apical bile salt export pump and multidrug resistance protein 2, using fluorescent probes and inhibitors, is a possible suggestion (Ramboer et al 2013;Yang et al 2016). …”
Section: Morphologymentioning
confidence: 99%